Given k = 1 ∏ 2 0 1 4 sin ( 2 0 1 5 k π ) = 2 b a . Find a 2 − b 2 .
Next : Product of This Year?? (Part 2) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Don't you think part-2 is incorrect?
The answer is 0 as at k = 1 0 0 7 , cos 2 0 1 4 k π = 0 , and hence, as a whole product is 0 . But infinite values of a and b satisfy.
Log in to reply
@jatin yadav Yes, thats what I was thinking as well.
and @Anish Puthuraya : I've fixed the problem part-2. You may want to solve it.
@Tunk-Fey Ariawan , you should change your status!
Nice solution Jatin.
you complicated it a bit , this solution is simple though uses same concepts as you did
Nice clean proof! In two instances, your denominator should be 2 n + 1 , not n
How did you get from sin 2 n k π to sin 2 2 n + 1 k π ??
Problem Loading...
Note Loading...
Set Loading...
Using sin θ = sin ( π − θ ) , It is quite easy to see that we are asked k = 1 ∏ 1 0 0 7 sin 2 ( 2 0 1 5 k π )
Let us generalize this problem(so that we can answer easily if the problem is asked again in 2016 :P)
We will prove that k = 1 ∏ n sin 2 ( 2 n + 1 k π ) = 2 2 n 2 n + 1
We know that x 2 − 2 x cos θ + 1 = ( x − e i θ ) ( x − e − i θ )
Also, roots of x 2 n + 1 = 1 are 1 , e ± 2 n + 1 2 i π , e ± 2 n + 1 4 i π , … e ± 2 n + 1 2 n i π
Hence, x 2 n + 1 − 1 = ( x − 1 ) k = 1 ∏ n ( x − e 2 n + 1 2 k i π ) ( x − e 2 n + 1 − 2 k i π )
Hence, 1 + x + … x 2 n = k = 1 ∏ n ( x 2 − 2 x cos n 2 k π + 1 )
Replacing x = 1 and using 1 − cos θ = 2 sin 2 2 θ for θ = n 2 k π , we have,
2 n + 1 = k = 1 ∏ n 4 sin 2 2 n + 1 k π = 2 2 n k = 1 ∏ n sin 2 2 n + 1 k π
Hence, k = 1 ∏ n sin 2 2 n + 1 k π = 2 2 n 2 n + 1
In our case, n = 1 0 0 7 , hence, answer is 2 2 0 1 4 2 0 1 5 .
Thus, a 2 − b 2 = ( a − b ) ( a + b ) = 4 0 2 9